Improving Estimation in Functional Linear Regression With Points of Impact: Insights Into Google AdWords. Issue 4 (1st October 2020) - Liebl, Dominik; Rameseder, Stefan; Rust, Christoph
Abstract: The functional linear regression model with points of impact (PoI) is a recent augmentation of the classical functional linear model with many practically important applications. In this article, however, we demonstrate that the existing data-driven procedure for estimating the parameters of this regression model can be very instable and inaccurate. The tendency to omit relevant PoI is a particularly problematic aspect resulting in omitted-variable biases. We explain the theoretical reason for this problem and propose a new sequential estimation algorithm that leads to significantly improved estimation results. Our estimation algorithm is compared with the existing estimation procedure using an in-depth simulation study. The applicability is demonstrated using data from Google AdWords, today's most important platform for online advertisements. The R-package FunRegPoI and additional R-codes are provided in the online supplementary materials .